Analyzing the profitability determinants of financial institutions: evidence from East Asian countries / Sadik Aden Dirir - Dirir, Sadik Aden (Universiti Teknologi MARA, Selangor, 2022)
Starting around 1960, Asia, the biggest and the most crowded place on the planet, has become wealthier compared to the rest of the world. Such growth and development definitely have not happened to other countries at a similar speed all around the continent. The western region of Asia has developed at a similar pace as the remainder of the world. However, the eastern region has grown to an unmatched level. With this in mind, this study aims to investigate the factors that determine and influence the profitability of the financial institution in East Asia. Panel data of eight East Asian countries were selected for the time frame between 2002 to 2021. Analysis of various factors that play an important role in altering the financial institution's profitability level was performed. These factors include the net interest margin, capital total assets, cost to income, non-performing loans, bank stability, the gross domestic product, and liquidity. The results displayed distinctive values. First, factors such as capital total assets, the stability of the bank, and gross domestic product revealed a significant influence on the net interest margin. Additionally, liquidity, the cost of income, nonperforming loans, and the gross domestic product presented a decrease in the level of net interest margin. This is acceptable for the liquidity and nonperforming loans since they have an inverse relationship with the net interest margin. On the other hand, a 1% increase in the capital total asset and the stability of the bank has enlarged the net interest margin by 0.05% and 0.04% successively. Hence, the results of this study may be valuable for other countries to consider in efforts to reshape their financial sector and monetary efficiency. The discoveries may also contribute significantly to the existing literature in this area since there is limited investigation concerning the East Asian region's financial sector.